Perancangan Sistem Informasi Checklist Kendaraan Menggunakan Metode Rapid Application Development (RAD) - Erman Arif; Ahmad Rais Ruli; Heri Riswanto (Journal on Education, 2023)
PT.Securindo Packatama Indonesia (Secure Parking) is the largest parking management service provider company in Indonesia located in Central Jakarta, DKI Jakarta. Technological developments are growing rapidly. And computers have had a considerable influence on both manufacturing companies and service companies, companies trade. The development of computer technology provides many advantages, one of the benefits that can be felt is the creation of a website that can help the process of interaction, marketing, or vehicle checklist input to be easier and more efficient. Securindo Packatama Indonesia is still done manually, thus allowing for a lack of efficiency during the process of making a vehicle checklist report. On this occasion the author provides a solution in the form of an example of designing a web-based system for companies in making checklist reports. vehicles and make it easier for employees to make vehicle reports to support operational efficiency. Therefore, by using the observation method, interviews, and library studies in data collection, the RAD method to analyze the running system, and the prototype method in software development, it is designed a web-based vehicle checklist information system. Making vehicle input activities and making vehicle reports more effective and practical because they can be done anywhere and anytime.